Case Report: Persistent COVID-19 in a fully vaccinated Japanese man being treated with rituximab and epcoritamab for diffuse large B-cell lymphoma - Suzuki, Masaki; Fujioka, Isao; Matsushima, Takamitsu (Frontiers in Medicine, 2025)
The management of persistent coronavirus disease 2019 (COVID-19) in patients with hematological malignancies who are immunocompromised because of underlying disease or iatrogenic immunosuppression remains clinically challenging. Herein, we report an 84-year-old man with stage 3 diffuse large B-cell lymphoma treated with rituximab and epcoritamab who subsequently developed persistent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, despite having received seven doses of COVID-19 mRNA vaccine and remdesivir. The patient was treated with a combination of remdesivir, sotrovimab, and nirmatrelvir/ritonavir, and recovered clinically. SARS-CoV-2 polymerase chain reaction and antigen tests eventually turned negative, and he was discharged after 28 days of hospitalization. This case highlights the challenges associated with managing persistent SARS-CoV-2 infection in immunocompromised patients with hematological malignancies. Combined treatment with antivirals and monoclonal antibodies may be an effective strategy.